Can Isaac Forgive Abraham?. Issue 1 (March 2017) - Gauvin, Mitchell J.
Abstract: Forgiveness is an expression that befits agents who are at heart morally frail and imperfect. There is strong disagreement regarding its structure, conditions, and permissibility. Søren Kierkegaard's pseudonymously authored Fear and Trembling —already well understood as a challenge to our understanding of faith, religion, and the moral law through its focus on the biblical tale of Abraham's binding of Isaac—offers an indirect challenge to our understanding of forgiveness. Isaac is too often overlooked as characterless and philosophically uninteresting. What such a reading ignores is his potential expression for what Kierkegaard understood as forgiveness: a dutiful commitment to love equally. Rather than dispelling traditional accounts of forgiveness, Isaac's binding reveals the extent of its diverse expressions.